Sprinting analysis of elite soccer players during European Champions League and UEFA Cup matches - Di Salvo, V.; Baron, R.; Gonzalez-Haro, C.; Gormasz, C.; Pigozzi, F.; Bachl, N. (Journal of Sports Sciences, 2010)
It has been suggested that assessment of high-intensity activities during a match is a valid measure of physical performance in elite soccer. Recently, sprinting activities have been analysed in more depth. The aim of this study was to develop a detailed analysis of the sprinting activities of different playing positions during European Champions League and UEFA Cup competitions. Altogether, 717 elite outfield soccer players were evaluated throughout 2002-2006 using ProZone® (Leeds, UK). Sprinting (explosive and leading) was analysed for each playing position. To compare positional differences, a Kruskal-Wallis analysis was performed. Differences were found among positions for total number of sprints and total sprint distance covered: wide midfielders > (attackers = wide defenders) > central midfielders > central defenders (P < 0.001), as well as for explosive sprints: (wide midfielders = attackers = wide defenders) > central defenders, wide midfielders > central midfielders > central defenders and attackers = wide defenders = central midfielders (P < 0.001), and leading sprints: wide midfielders > (attackers = wide defenders) > central midfielders > central defenders (P < 0.001). For each group, there were no differences in ratio of explosive to leading sprints. Wide midfielders performed a higher number of sprints in all five distance categories than all other positions. This study showed that sprinting characteristics are influenced by position. Wide midfielders have to complete additional high-intensity activities during training sessions compared with the other positions to achieve the performance level required during the match.